Indonesia PENGARUH KUALITAS AUDIT, PROFITABILITAS DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PADA TAHUN 2017-2020: Indonesia - Raynaldo Stefanus Herikusnanto; Lorina Siregar Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
ABSTRACT.Firm value is the selling price or price of the company when the company is sold to potential buyers and investors and is usually reflected in the price of shares sold by the company. If the company's value is good, investors will think that the company is good too. This study determines the effect of audit quality, profitability, and solvency on firm value. The data is taken from food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2020 period. The total research sample in this article is 17 sample companies so that the total data for this research is 72. The analytical tool used is SPSS 23. This research has obtained a result that shows audit quality, profitability and solvency not have an affect on firm value. Keywords: Audit Quality, Profitability, Solvency, Firm Value.